Are we doing it right? Self-care support for patients with type 2 diabetes in urban areas in Malaysia - Saidi, Sanisah; Milnes, Linda J.; Griffiths, Jane (Elsevier, 2019)
Objective The purpose of this study is to explore the self-care support provision for patients with type 2 diabetes by diabetes educators and to explore the challenges that they encountered in providing the intended services.